Konseling Individu Terhadap Siswa yang Kesulitan Komunikasi - Wahyu, Maulana Nur; Nur Hermatasiyah; Muhammad Fauzan Muttaqin (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
This research aims to evaluate the communication challenges faced by fifth grade students in elementary schools through a case study approach. The research method used is qualitative with a focus on case studies. Data collection was carried out through observing the student counseling process, interviews with 5th grade elementary school teachers, and documenting the results of individual counseling assessments. Research subjects were selected using a purposive sampling method. Data validation uses triangulation of sources and techniques. Data analysis is carried out through interactive analysis which includes data collection, reduction, data display and drawing conclusions. The research results show that individual student counseling is carried out through an initial stage which includes relationship building and counseling principles, a core stage which includes problem exploration and reassessment, and a final stage which includes action planning and evaluation of the counseling process and results. Students experience gradual changes in communication skills, so they can interact with other students better and more confidently. The counseling approach applied by teachers has a key role in helping students overcome barriers to communication. The implication is that teachers can develop better communication skills and increase students' self-confidence in interacting in the school environment and outside the classroom.